Is Employability Displacing Higher Education? - Marginson, Simon (International Higher Education, 2024)
Employability is becoming embedded in mass higher education with considerable moral authority. Everybody wants a job, and work is seen as a human right. However, higher education is not very effective in direct preparation for work, it cannot create jobs, and the mantra of employability blocks from view its core educational mission, which is student self-formation through immersion in knowledge. This is emerging as an existential crisis for the sector.